Estimation of electric field fluctuations below the auroral ionosphere - Oguti, Takasi; Hayashi, Kanji (1985)
P(論文) A fluctuation in an electric field below a pulsating aurora, as well as an electric field intensity below a discrete aurora (vortex-chain aurora), or an auroral ionosphere where an electric field is applied from the magnetospheric convection, was estimated at a 30km altitude (possible balloon altitude) and on the ground by a theoretical model. The results show that the electric field fluctuation, corresponding to an auroral pulsation, is usually as small as a few percents and a few tens of percent, respectively, of the ionospheric electric field when measured at a 30km altitude and on the ground when the size of the pulsating auroral patch is 50km across. On the other hand, the electric field below the ionospheric, related to a discrete aurora or convection electric field above, is shown to amount to the value almost equal to, and 20 times larger than, the ionospheric value respectively at the 30km altitude and on the ground, if a north-south, uniform or convergent electric field exists in an east-west elongated belt, 200km in width, in the ionosphere. It is also shown that the values of the electric field and its fluctuation both at the 30km altitude and on the ground depend largely on the size of the spatial extent of the electric field in and above the ionosphere. These results suggest that the electric field fluctuation related to the auroral pulsation is measured only by the multiple correlation method taking the all auroral patches within range into consideration even when the size of auroral patch is greater than tens of km. The calculation also suggests that the electric field related to a discrete aurora or the convection electric field could be measured by taking a spatial correlation and/or multiple correlations with auroral variations of electric field fluctuations obtained at ground network stations below the auroral ionosphere. departmental bulletin paper